Improvement of Quality of Customs Services and Customs Control of the Goods Moved by Individuals for Private Use at Air Check Points - I. V. Grekov (Управленческое консультирование)
The article considers issues of efficiency of customs control in the framework and quality of customs services. Analyzes the international experience of implementation of customs control of goods for personal use exported by physical persons in air checkpoints. Focuses on the development of guidelines, aimed at regulating «non-trade turnover of goods» for the personal use of individuals in air checkpoints. Described the scientific and practical insights to solve problems.